Pregnancy and urinary infection health center expansion Paucarpata - Jannet Escobedo Vargas (2019)
Urine tract infection is the most frequent infectious condition during pregnancy and may result in severe consequences for mother, fetus and newborn.This study tries to determine the features of urine tract infections in pregnant patients attending the prenatal clinic in the Ampliacion paucarpata health center of the ministry of health . Our objectives were:To determine the rate of urine infections, to identify the most frequent causative organisms , and to determine the sensitivity to antibiotics used in treatment of UTIs.It was descriptive, prospective, cross sectional study, with a sample of 88 pregnant patients between 12 and 40 gestational weeks, any parity with or without urine infection symptoms seen in the outpatient office between March and December 2010 .Urine samples were collected after giving their informed consent . Samples were studied by sedimentation, complete urine examination and urine culture and antibiogram. Pregnant women taking antibiotics at the moment of the examination were excludedAntibiotic sensitivity was determined by Kìrby-Bauer method (Antibiotic dissuion disks method).Frequency of urinary infection in this group was 12.5% (88 cultures) . Most frequent isolated bacterium was E. Coli (72.7%) similar to other studies both national amd international.Escherichia coli was sensitive in 100% to ceftriaxone, cephalotin, gentamicin, amykacin, and ceftazidime.63.6% cases with positive urine cultures did not show any symptoms (asymptomatic bacteriuria). 27.3% of positive urine cultures had normal sediments.Our recommendation is to perform routine urine cultures to all pregnant patients because of cases of asymptomatic bacteriuria and positive urine cultures with normal sedimentation exam